Pullulan Films Containing Rockrose Essential Oil for Potential Food Packaging Applications - Luís, Ângelo (2020)
Active packaging is designed to control the development of decay- and disease-causing microorganisms and is emerging as a promising technology for extending shelf-life, maintaining food safety, reducing waste, and minimizing the risks for foodborne diseases. The goal of this work was to develop and characterize bioactive pullulan-based films, containing rockrose (Cistus ladanifer) essential oil. Among other abundant compounds (camphene, bornyl acetate and trans-pinocarveol), α-pinene was identified as the major compound of rockrose essential oil (39.25%). The essential oil presented stronger antibacterial activity against Gram-positive than against Gram-negative bacteria. The antioxidant results indicate the potential of the developed films to be used to package foods susceptible to oxidation and rancification, thus improving their shelf-life. Also, this study reflects the potential of rockrose essential oil, free or incorporated in pullulan, as a promising quorum sensing inhibitor, since it was able to interrupt intercellular communication, inhibiting violacein production. Electronic microscopy images showed the antibiofilm activity of the films with rockrose essential oil that were able to influence bacterial adhesion, which may be explained by the differences in the surface free energy of the films, as also determined.